Gender Inequality Experienced by Jo March in the Film “Little Women (2019)” - Angelia, Feby; Widyaningrum, Agnes (Surakarta English and Literature Journal, 2024)
This research investigated the forms of gender discrimination experienced by the female character Jo March in the film "Little Women (2019)" and Jo's efforts against the discrimination in her societal life during the post-Civil War era in America. The study is conducted through a contextual approach and utilizes Simone de Beauvoir's feminist study approach. This research identifies the forms of discrimination experienced by the character Jo March in aspects of work, life, and family. Additionally, the research also reveals the forms of resistance carried out by Jo March in confronting gender discrimination including (1) continuing her work; (2) rejecting gender conventions; (3) pursuing independence in education and financial matters; and (4) advocating for women's rights. This research provides insights into the gender inequality faced by women in America at that time. The findings are expected to inspire women to further advocate for their rights and not give up in the face of the discrimination they experience. This study contributes to the field of gender studies by highlighting the pervasive impact of patriarchal norms on gender discrimination, thereby inspiring women to advocate for their rights and fostering a deeper understanding of gender equality. Additionally, it offers valuable insights for future research, encouraging a broader exploration of feminist issues and the diverse cultural contexts affecting women's roles and autonomy.